2006
DOI: 10.1038/sj.bjp.0706727
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ERK1/2 activity by ghrelin‐activated growth hormone secretagogue receptor 1A involves a PLC/PKCɛ pathway

Abstract: 1 The growth hormone secretagogue receptor 1a (GHSR-1a) is a G-protein coupled receptor, involved in the biological actions of ghrelin by triggering inositol phosphates and calcium intracellular second messengers. It has also been reported that ghrelin could activate the 44-and 42-kDa extracellular signal-regulated protein kinases (ERK1/2) in different cell lines, but it is not clear whether this regulation is GHSR-1a dependent or not. 2 To provide direct evidence for the coupling of GHSR-1a to ERK1/2 activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 94 publications
2
44
0
Order By: Relevance
“…The KCNQ/M-current deactivation kinetics features KCNQ2 channels that have been shown to be expressed in nigral dopaminergic neurons 15,18 . In addition, although previous studies have shown that the signal transduction pathway for ghrelin is mediated by PLC/PKC in non-neuronal tissues and cell lines 13,27,28 , our findings first demonstrated that PKC is involved in the effects of ghrelin in native neurons. The signalling transduction pathway of how ghrelin promotes nigral neuronal firing is summarized in Supplementary Fig.…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelinmentioning
confidence: 72%
See 1 more Smart Citation
“…The KCNQ/M-current deactivation kinetics features KCNQ2 channels that have been shown to be expressed in nigral dopaminergic neurons 15,18 . In addition, although previous studies have shown that the signal transduction pathway for ghrelin is mediated by PLC/PKC in non-neuronal tissues and cell lines 13,27,28 , our findings first demonstrated that PKC is involved in the effects of ghrelin in native neurons. The signalling transduction pathway of how ghrelin promotes nigral neuronal firing is summarized in Supplementary Fig.…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelinmentioning
confidence: 72%
“…KCNQ channels are also negatively modulated by G-protein-coupled receptors via Gq and/ or G 11 activated phospholipase C (PLC)-mediated signal pathway [24][25][26] . It has also been reported that the effects of ghrelin are mediated by PLC that hydrolyses PIP 2 for IP 3 signalling in hypothalamus 13 , or by protein kinase C (PKC) in non-neuronal tissues and cell lines 27,28 , ultimately affecting potassium channel conductance 29 . All these observations suggest that ghrelin signalling is likely coupled with neuronal KCNQ/ M-channel function.…”
mentioning
confidence: 99%
“…both through most G-protein pathways and through G-protein-independent pathways, of which ␤-arrestin-mediated ERK1/2 activation is the most well described mechanism (15,19). It has been suggested that ghrelin-induced ERK1/2 phosphorylation involves phospholipase C and PKC⑀ activation (45) but that it is independent of internalization and ␤-arrestin (46). The fact that the pharmacological profiles for ghrelin and wFw-Isn-NH 2 are very similar in the signaling pathways analyzed in the present study would suggest that the ERK1/2 activation results from G␣ q coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin also stimulates cell proliferation by activating several different pathways, including the mitogen-activated protein kinase (MAPK), extracellular signal-regulated protein kinases (ERK1/2), the transcriptional factor Elk1 [37], through the Akt/PI3K signaling [38] and through a tyrosinekinase dependent pathway [22]. Another different pathway for ghrelin action is the nitric oxide (NO)/cGMP signaling pathway, that promotes vasodilation [39,40].…”
Section: Ghrelin Receptorsmentioning
confidence: 99%
“…After its activation GHSR-1a promotes the activation of phospholipase C (PLC), phosphatidyl-inositol-4,5-biphosphate hydrolysis with the formation of diacylglyceride (DAG) and inositol triphosphate (IP 3 ). While IP 3 promotes a transient elevation of intracellular calcium from the sarcoplasmatic reticulum, DAG induces depolarization by the inhibition of potassium channels and opening of the voltage-dependent L-type calcium channels of the cellular membrane [36].Ghrelin also stimulates cell proliferation by activating several different pathways, including the mitogen-activated protein kinase (MAPK), extracellular signal-regulated protein kinases (ERK1/2), the transcriptional factor Elk1 [37], through the Akt/PI3K signaling [38] and through a tyrosinekinase dependent pathway [22]. Another different pathway for ghrelin action is the nitric oxide (NO)/cGMP signaling pathway, that promotes vasodilation [39,40].…”
mentioning
confidence: 99%